2020
DOI: 10.1515/anona-2020-0151
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity and concentration behaviour of solutions for a fractional Choquard equation with critical growth

Abstract: In this paper, we study the singularly perturbed fractional Choquard equation $$\begin{equation*}\varepsilon^{2s}(-{\it\Delta})^su+V(x)u=\varepsilon^{\mu-3}(\int\limits_{\mathbb{R}^3}\frac{|u(y)|^{2^*_{\mu,s}}+F(u(y))}{|x-y|^\mu}dy)(|u|^{2^*_{\mu,s}-2}u+\frac{1}{2^*_{\mu,s}}f(u)) \, \text{in}\, \mathbb{R}^3, \end{equation*}$$ where ε > 0 is a small parameter, (−△)s denotes the fractional Laplacian of order s ∈ (0, 1), 0 < μ < 3, $2_{\mu ,s}^{\star }=\frac{6-\mu }{3-2s}$is the critical exponen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…We also want to mention some recent work about multiplicity for Choquard equations dealing with concentration properties. Yang and Zhao [28] applied penalization techniques and Ljusternik-Schnirelmann theory to investigate the relation between the number of positive solutions and the topology of the set where the potential attains its minimum values for a singularly perturbed fractional Choquard equation, and showed that these positive solutions locate at the minimum point of the potential. In addition, Cingolani and Tanaka [8] studied the multiplicity and concentration of positive single-peak solutions for a nonlinear Choquard equation, and they used relative cup-length to estimate the topological changes and then related the number of positive solutions to the topology of the critical set of the potential.…”
Section: Introduction and A Main Resultsmentioning
confidence: 99%
“…We also want to mention some recent work about multiplicity for Choquard equations dealing with concentration properties. Yang and Zhao [28] applied penalization techniques and Ljusternik-Schnirelmann theory to investigate the relation between the number of positive solutions and the topology of the set where the potential attains its minimum values for a singularly perturbed fractional Choquard equation, and showed that these positive solutions locate at the minimum point of the potential. In addition, Cingolani and Tanaka [8] studied the multiplicity and concentration of positive single-peak solutions for a nonlinear Choquard equation, and they used relative cup-length to estimate the topological changes and then related the number of positive solutions to the topology of the critical set of the potential.…”
Section: Introduction and A Main Resultsmentioning
confidence: 99%
“…The first equation in (1.2) was introduced by Laskin (see [21,22]) and comes from an expansion of the Feynman path integral from Brownian-like to Lévy-like quantum mechanical paths. This class of fractional Schrödinger equations with a repulsive nonlocal Coulombic potential is obtained by approximation of the Hartree-Fock equation describing a quantum mechanical system of many particles; see, for instance, [14,23,24,38]. It also appeared in several areas such as optimization, finance, phase transitions, stratified materials, crystal dislocation, flame propagation, conservation laws, materials science and water waves (see [9]).…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…Mathematically, doubly nonlocal equations have been treated in [25,26] in the case of pure power nonlinearities (see also [15] for some orbital stability results and [14] for a Strichartz estimates approach), obtaining existence and qualitative properties of the solutions. Other results can be found in [72,5,61] for superlinear nonlinearities, in [40] for L 2 -supercritical Cauchy problems, in [38] for bounded domains and in [77] for concentration phenomena with strictly noncritical and monotone sources.…”
Section: Introductionmentioning
confidence: 88%